Identification of treatment‐induced vulnerabilities in pancreatic cancer patients using functional model systems. Issue 4 (4th February 2022) - Peschke, Katja; Jakubowsky, Hannah; Schäfer, Arlett; Maurer, Carlo; Lange, Sebastian; Orben, Felix; Bernad, Raquel; Harder, Felix N; Eiber, Matthias; Öllinger, Rupert; Steiger, Katja; Schlitter, Melissa; et al.
Abstract: Despite the advance and success of precision oncology in gastrointestinal cancers, the frequency of molecular‐informed therapy decisions in pancreatic ductal adenocarcinoma (PDAC) is currently neglectable. We present a longitudinal precision oncology platform based on functional model systems, including patient‐derived organoids, to identify chemotherapy‐induced vulnerabilities. We demonstrate that treatment‐induced tumor cell plasticity in vivo distinctly changes responsiveness to targeted therapies, without the presence of a selectable genetic marker, indicating that tumor cell plasticity can be functionalized. By adding a mechanistic layer to precision oncology, adaptive processes of tumors under therapy can be exploited, particularly in highly plastic tumors, such as pancreatic cancer. Synopsis: Therapy resistance remains a major challenge in pancreatic cancer. This study used patient‐derived organoids (PDOs) and cell lines (PDCL) to investigate response to standard‐of‐care chemotherapy administered in humans. We show that chemotherapy‐induced adaption exposes novel therapeutic vulnerabilities accompanied by cellular re‐differentiation. Longitudinal generation of pancreatic cancer PDOs allows to study treatment‐imposed plasticity. Treatment‐induced non‐genetic mechanism impact on cellular plasticity and therapeutic vulnerabilities. Differentiation within the EMT spectrum of tumor cells upon chemotherapy is not restricted to acquisition of mesenchymal phenotypes but allows epithelial re‐differentiation. Abstract : Therapy resistance remains a major challenge in pancreatic cancer. This study used patient‐derived organoids (PDOs) and cell lines (PDCL) to investigate response to standard of care chemotherapy administered in humans. We show that chemotherapy‐induced adaption exposes novel therapeutic vulnerabilities accompanied by cellular re‐differentiation.